Pengenalan Prototype Kumbung Jamur Merang Berbasis Internet of Things Pada Desa Gempol Kolot - Masruriyah, Anis Fitri Nur (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
One of the impacts of the COVID-19 pandemic in Karawang Regency is the reduction of employees and cutting costs on mushroom cultivation. This has an impact on the monitoring period for mushrooms, mushroom farmers who have to enter the mushroom kumbung with higher temperature and humidity outside the kumbung. Prior to the pandemic, the monitoring employees took turns checking the condition of the mushrooms, but due to the pandemic and the limited number of employees, farmers were overwhelmed. Based on these problems, the introduction of technology in the form of a prototype of kumbung mushroom based on the internet of things was carried out to help mushroom cultivators. The recommendation given to mushroom farmers is to implement an IoT system to help increase the number of harvests and shorten harvest time. Furthermore, for the implementing team for community service and universities, it is to find a solution to create an economical system. So that mushroom farmers are not burdened with system installation costs.